Prison Strains, Negative Emotions, and Deviance Among Prisoners in South Korea: a Latent-Variable Modeling Test of General Strain Theory - Jang, Sung Joon (International journal of offender therapy and comparative criminology, 2020)
This article examines the applicability of general strain theory to correctional samples by testing whether prison strains are positively related to deviance among prisoners through strain-associated negative emotions and whether the negative emotions-deviance relationship is systematic in terms of inner versus outer directedness. Latent-variable structural equation modeling was applied to analyze survey data from 986 male prisoners in South Korea. First, an inmate’s dissatisfaction with correctional officers was found to be positively related to anger and fear of victimization, whereas in-prison victimization was related only to the fear. Second, outer-directed emotion (anger) was positively related to outer-directed deviance (aggressive and property misconduct and anticipated reoffending) but not to inner-directed deviance (self-injury/suicide attempt). On the contrary, inner-directed emotion (fear) was related positively to the inner-directed deviance but inversely to property misconduct. Finally, some of the indirect relationships of victimization and dissatisfaction with deviance via negative emotions were found to be significant.